2010
DOI: 10.2217/pme.10.23
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic-Based Survey of Public Attitudes Towards Predictive Genetic Testing in Russia

Abstract: Many new genetic tests for common multifactorial disorders are becoming available to individuals, including direct-to-consumer genotyping services. Typically, studies of public attitudes reveal a high level of interest for individual genotyping. In a Russian urban population, 85% of 2000 respondents answered positively to a question about their own willingness to undergo predictive genetic testing for preventable health conditions. Gender, age and health status significantly influenced response. Multivariate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
6
25
0
2
Order By: Relevance
“…Interest in genetic testing has been described, in particular also for multifactorial diseases in which the contribution of genes is rather low. 14,15,21 Increasing use of testing is thus expected, in particular with decreasing costs of testing. 14 We are now entering a new period in genetics as sequencing becomes cheaper and whole genome sequencing is being used in clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in genetic testing has been described, in particular also for multifactorial diseases in which the contribution of genes is rather low. 14,15,21 Increasing use of testing is thus expected, in particular with decreasing costs of testing. 14 We are now entering a new period in genetics as sequencing becomes cheaper and whole genome sequencing is being used in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…11 Attitudes towards genetic testing vary with age, gender and educational level. Overall, younger people seem to show a higher interest in genetic testing, [13][14][15] and have more positive attitudes. 13,16 Men seem to have more positive attitudes towards testing, 10,13 but some studies have indicated that women are more knowledgeable on genetics.…”
Section: Introductionmentioning
confidence: 97%
“…However, limited evidence is available regarding the attitude of health professionals towards riboflavin as a targeted treatment option for BP management. In recent years, there is increasing public interest in genetic testing in the health field, in a study investigating attitudes to genetic testing among 2000 individuals, 81 % of respondents believed that knowing their genetic risk could lead to better control of their lives (108) . A number of studies have reported that individuals identified as having a higher disease risk through genetic testing may be more motivated to change dietary habits (109)(110)(111) .…”
Section: Mechanism Of Mthfr C677t Polymorphism Riboflavin and Blood mentioning
confidence: 99%
“…This situation implies that a number of different strategies should be employed to enhance the potential societal and individual benefits of genomic medicine, by obtaining a better understanding on of how the general public and healthcare professionals perceive genetic services and genetics in general and genetic services in particular. So far, very few studies have been undertaken in a handful of European populations, namely in Finland [4], Germany [5] and Russia [6]. Recently, we reported our findings from similar nationwide surveys in Greece, to evaluate the services provided and the operational principles of private genetic laboratories [7] as well as to ascertain the views of both physicians' and the general public's views on genetics and genetic testing services [8].…”
Section: Introductionmentioning
confidence: 96%